Analiza elektrokemijskega šuma, generiranega z različnimi korozijskimi procesi - Bajt Leban, Mirjam (Kovine zlitine tehnologije, 1998)
In the present study the characteristics of electrochemical noise generated by different types of corrosion have been examined. The potential and current noise have been measured between three identical electrodes made from the same material (AISI 302) in aqueous solutions with different concentration of chlorides and/or additions of acid at the higher temperature. The common electrode was under tensile load. The optical microscope supported by a computer visualization technique was used simultaneously during the tests and compared with signals of electrochemical noise generated at the same time. In order to characterise the measured signals, and especially to distinguish between the signals of electrochemical noise generated by pitting corrosion, stress-corrosion cracking and uniform corrosion, various parameters known from the fractal theory and theory of chaos were estimated. It is concluded that the electrochemical noise measurements and analysis can distinguish between uniform corrosion and different types of localised corrosion. We can detect breakdown of passive film, repassivation and growth of stable pitts. We can also detect the initiation of cracks, but we still cannot follow to the propagation of cracks
Keywords: elektrokemija; korozija; šum; merjenje; elektrokemijski šum; preiskava materiala